Geovisualization with immersive virtual environments in theory and practice. Issue 2 (1st February 2019) - Hruby, Florian; Ressl, Rainer; de la Borbolla del Valle, Genghis
ABSTRACT: Virtual reality (VR) is a frequently emphasized issue on the Digital Earth (DE) agenda. While current DE research is more engaged in the technical aspects of VR applications, this paper focuses on what is possible with immersive virtual environments (IVE) from the user's perspective. After a brief discussion of spatial presence and embodiment in the context of IVE, both concepts will be merged into a geovisualization immersion pipeline (GIP) as a framework with which to systematically link technical and cognitive aspects of IVE. We will then analyze the general criteria that must be met by IVE in order to facilitate the experience of spatial presence. Adapting these criteria to the special requirements of geospatial data, a definition of geovisualization immersive virtual environments (GeoIVE) is formulated. Finally, the theoretical considerations of this paper are set into practice, using a GeoIVE of a coral reef ecosystem as an example. As we shall see, while GIS do not provide data models or data compatibility for direct visualization of GeoIVE on VR output devices, game engines can serve as middleware to fill this gap.